(untitled) (Historia, 2021)
No. Of course not. It’s not water, or oxygen, or the trees. it’s not even crucial to good scholarship. For thousands of years we’ve been making meaningful discoveries about the world without going digital. Do you need the digital history is the wrong question. Even digital history itself is the wrong phrase, because at its core, digital history is symbolic of something: interdisciplinarity.